Taking ownership: The implementation of a non-aboriginal program for on-reserve children - Beatch, Michelle (2006)
In this qualitative study, I assessed the appropriateness of a non-Ahoriginal early childhood education intervention, the Home Instruction for Parents of Preschool Youngsters (HIPPY) program in 5 on-reserve First Nations communities, by focusing on the experiences of the program employees. Findings from ~ndividual and focus group interviews and researcher observations revealed a process of 'taking ownership' of the HIPPY program by these women. 'Taking ownership' included three sub-processes: (1) views regarding the strength of the program shifted from children's school readiness skills to supporttng cultural pride and awareness; (2) the women's self-identities moved from cultural disconnectedness to a strengthened Aboriginal identity; and (3) whether HIPPY is Aboriginal became an increasingly important issue for these women because they, as Aboriginal women, delitrered it. By taking ownership of and culturally contextualizing the HIPPY program these women have further ensured its appropriateness for their communities.